2023
DOI: 10.1007/s11926-023-01125-6
|View full text |Cite
|
Sign up to set email alerts
|

Role of IFN-α in Rheumatoid Arthritis

Chung M. A. Lin,
John D. Isaacs,
Faye A. H. Cooles

Abstract: Purpose of Review Type 1 interferons (IFN-I) are of increasing interest across a wide range of autoimmune rheumatic diseases. Historically, research into their role in rheumatoid arthritis (RA) has been relatively neglected, but recent work continues to highlight a potential contribution to RA pathophysiology. Recent Findings We emphasise the importance of disease stage when examining IFN-I in RA and provide an overview on how IFN-I may have a direct role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 125 publications
(117 reference statements)
0
2
0
Order By: Relevance
“…Type 1 INF (IFNα) has also been shown to play an important role in the pathogenesis of SAIDs and is of increasing interest to researchers as a therapeutic target (Figure 2) [30,123,124]. Anifrolumab is an immunoglobulin gamma 1 kappa (IgG1κ) mAb that targets subunit 1 of INFAR1 and therefore blocks IFN-α and IFN-β signaling (Table S3) [124].…”
Section: Common Therapeutics For Sle Ssc and Ramentioning
confidence: 99%
See 1 more Smart Citation
“…Type 1 INF (IFNα) has also been shown to play an important role in the pathogenesis of SAIDs and is of increasing interest to researchers as a therapeutic target (Figure 2) [30,123,124]. Anifrolumab is an immunoglobulin gamma 1 kappa (IgG1κ) mAb that targets subunit 1 of INFAR1 and therefore blocks IFN-α and IFN-β signaling (Table S3) [124].…”
Section: Common Therapeutics For Sle Ssc and Ramentioning
confidence: 99%
“…Similar to SLE, anifrolumab has shown efficacy in the treatment of SSc and is now in a Phase III clinical trial (Table S3). Clinical trials for RA reported that future larger studies are needed to assess the efficacy of this drug in RA [123,126].…”
Section: Common Therapeutics For Sle Ssc and Ramentioning
confidence: 99%